Luring the Dragon’s Neighbor: the Biden Administration’s Strategies to Engage Vietnam against an Ambitious China - Vu, Van-Hoa; Nguyen, Khac-Nghia (Journal of Posthumanism, 2025)
Amid the intensifying US-China strategic rivalry, the Biden administration has placed significant emphasis on strengthening key partnerships within the Indo-Pacific. Central to this strategic recalibration is Vietnam, a nation once considered a challenger, now emerging as a critical player in Washington’s regional strategy. This paper seeks to unpack the complexities of US engagement with Hanoi, analyzing three pivotal policy domains—politics and diplomacy, security and defense, and economics and trade—through which the US aims to deeply integrate Vietnam into its regional framework and counterbalance China’s growing influence. The analysis explores both the concrete advances and the more subtle shifts currently unfolding in this bilateral relationship. Over time, Vietnam has incrementally moved closer to the US, signaling a significant transformation in its foreign policy. Despite the Biden administration’s efforts to enhance the appeal of bilateral ties, Vietnam remains cautious and carefully weighs its steps in advancing relations with the US.